2022
DOI: 10.1371/journal.pone.0262635
|View full text |Cite
|
Sign up to set email alerts
|

Developing the Breast Utility Instrument, a preference-based instrument to measure health-related quality of life in women with breast cancer: Confirmatory factor analysis of the EORTC QLQ-C30 and BR45 to establish dimensions

Abstract: Objectives Breast cancer (BrC) and its treatments impair health-related quality of life (HRQoL). Utility is a measure of HRQoL that includes preferences for health outcomes, used in treatment decision-making. Generic preference-based instruments lack BrC-specific concerns, indicating the need for a BrC-specific preference-based instrument. Our objective was to determine dimensions of the European Organisation for Research and Treatment of Cancer (EORTC) general cancer (QLQ-C30) and breast module (BR45) instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 51 publications
(74 reference statements)
1
16
0
Order By: Relevance
“…It has 45 items, 23 of which are from the original QLQ-BR23, and has been translated into 19 languages (35). The English version of this questionnaire has been tested and found to be valid in Western countries (36,37); however, no specific validation and translation for Asian countries, including Indonesia, has been completed. To be able to translate the instrument into a good instrument in the target language, strategies should be applied to increase the accuracy of semantic equivalence with the target population, as well as to increase the conceptual accuracy where the concept of the source text is conveyed accurately and by taking the norms and culture of target population into account (38,39).…”
mentioning
confidence: 99%
“…It has 45 items, 23 of which are from the original QLQ-BR23, and has been translated into 19 languages (35). The English version of this questionnaire has been tested and found to be valid in Western countries (36,37); however, no specific validation and translation for Asian countries, including Indonesia, has been completed. To be able to translate the instrument into a good instrument in the target language, strategies should be applied to increase the accuracy of semantic equivalence with the target population, as well as to increase the conceptual accuracy where the concept of the source text is conveyed accurately and by taking the norms and culture of target population into account (38,39).…”
mentioning
confidence: 99%
“…This resulted in improved reliability (PSI = 0.784). SYS37 ( Hot flushes ), assigned to endocrine therapy from the confirmatory factor analysis, 25 was retained because it was rated most important by patients despite its high infit (1.81) and outfit (3.12) and uniform DIF (likelihood ratio χ 2 P = 0–0.419, McFadden’s pseudo R 2 = 0.001–0.023). Three items with low infit and outfit (<0.70) were retained ET63 ( Problems with your joints ), ET64 ( Stiffness in your joints ), ET65 ( Pain in your joints ) since iterative removal lowered model reliability (PSI < 0.7).…”
Section: Resultsmentioning
confidence: 99%
“…The sequence of applying the item importance approach could have influenced the final section of items. Patients and clinicians were asked to complete item importance ratings prior to our confirmatory factor analysis, 25 and the ranking of mean item importance ratings were considered in our final selection of each item per dimension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Item importance surveys like the one employed in this study have been demonstrated to be a reliable means of item selection for this purpose (7,8). The use of factor analysis and IRT in the generation of condition-specific utility instruments is a subject of ongoing research (20).…”
Section: Discussionmentioning
confidence: 99%